PENERAPAN ROUTER DAN ACCESS POINT SEBAGAI MEDIA PROMOSI WISATA PROVINSI NUSA TENGGARA TIMUR - Belutowe, Yohanes Suban (STIKOM Uyelindo Kupang, 2019)
East Nusa Tenggara Province is one of the tourist destination areas, one of its prima donnas is Komodo Island which was included in the list of The New 7 Wonders of Nature in 2012. But not only that, there are still many stunning tourist destinations. Kupang City is the main destination before accessing the natural beauty of the East Nusa Tenggara region. In the Kupang City and the Regency of Kupang itself holds many tourist destinations, but the terms of promotion that are still catalog and social media are deemed inadequate. High cost of catalog production and data costs for accessing social media are not cheap either. But by using a router and access point, it is expected that these costs can be eliminated. The router is used to create a hotspot login page. The login page can be modified into a digital catalog (website page) while the Access Point is used to distribute catalog. Hotspots can be accessed free of charge by tourist attractions. Digital catalog can be changed according to the development of tourist attractions. This digital catalog also provides alternative tourism in the Kupang City and other areas in East Nusa Tenggara Province